ANALISIS PERUBAHAN GARIS PANTAI DI WILAYAH PESISIR KECAMATAN SOROPIA - Rahmat Ucok; Sawaludin; Nurgiantoro (Sustainability (STPP) Theory, Practice and Policy, 2024)
The coastal environment is a dynamic area constantly undergoing changes due to various natural and anthropogenic factors. These changes can occur slowly or rapidly, influenced by elements such as wave action, tides, human activities, and climatic events. Monitoring these changes is essential for effective coastal management. This study aims to: (1) Analyze changes in coastlines in Soropia Sub-district between 2013 and 2022; and (2) Identify the factors influencing these changes. Landsat 8 imagery was used for this research, analyzed using the Overlay method to detect and quantify coastal changes over the nine-year period. The results indicate that four areas in Soropia Sub-district experienced significant coastline changes. The most substantial accretion occurred in Bajo Indah Village with a change of 130 meters, while the smallest accretion was observed in Toronipa Village with a change of 26 meters. Toronipa Village also experienced minor abrasion with a change of 0.3 meters. The factors influencing these changes include sediment accumulation, currents, wave height, and reclamation activities. This study provides valuable insights into coastal dynamics in Soropia Sub-district and highlights the importance of continuous monitoring and comprehensive analysis to inform future coastal management strategies.